Atenção à saúde das pessoas expostas ou intoxicadas : análise das práticas de atenção pela perspectiva da Rede de Atenção à Saude = Health care of exposed or intoxicated people: analysis of the health practices from the perspective of the health care network - Costa, Aline de Oliveira, 1987- (2019)
Orientador: Herling Gregorio Aguilar Alonzo